30.7k views
5 votes
If h(x)=3^x then h (-4) =

User Sven Rusch
by
5.5k points

2 Answers

6 votes

Answer:

1/81

Explanation:

In h(x)=3^x, replace each instance of x with -4:

h(-4) = 3^(-4), or

1

h(-4) = ----------- = 1/81

3^4

User Katye
by
4.8k points
5 votes


\huge{\mathbb{\tt { PROBLEM:}}}

if h(x)=3^x then h (-4) =


\huge{\mathbb{\tt { ANSWER:}}}


(1)/(81)


\huge{\mathbb{\tt { EXPLANATION:}}}

In h(x) = 3^x , you must replace each instance of with -4:

h(-4)=3^(-4)


h(4)= (1)/(3^4) = (1)/(81)

#CarryOnLearning

#LetsEnjoyTheSummer

X x K i m 0 2 x X

User Manav Sharma
by
6.2k points